PENYEGARAN USAHA KESEHATAN SEKOLAH (UKS) UNTUK PENCEGAHAN KECACINGAN DI MASA PASCA PANDEMI COVID-19 - Lies Permana; Evi Andriani (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
According to the WHO, Asia has the highest number of soil-transmitted helminth infections (STH), including Indonesia included. Children between the ages of 1 and 12 in Indonesia have the highest worm infection rates. Children's health is impacted by the frequent disregard for clean and healthy behavior (PHBS) in educational settings. The implications of not doing PHBS include the spread of infectious illnesses, including helminthiasis and diarrhea. Students at this institution are believed to have poor hygiene habits and unhealthy lifestyle choices, which increases their chance of contracting infectious disorders like helminthiasis. The development of PHBS in enhancing student health should be done through Schoolâ€™s Health Clinic (UKS). The COVID-19 pandemic has stopped almost all schooling activities, including the implementation of UKS. It is necessary to make efforts to renew UKS by delivering health education regarding PHBS in order to prevent infectious diseases in the wake of the COVID-19 pandemic. The PRECEDE-PROCEED framework is used to carry out community service, beginning with identifying and assessing issues within the PRECEDE framework, collaborating with schools and health facilities to identify problem-solving programs, and then completing the service. In order to improve their knowledge of PHBS in avoiding worms, health education is carried out via the lecture technique and the use of leaflet media. In December 2022, the exercise was conducted with third-grade students from elementary school. using a 10-question pretest and posttest to compare the effectiveness of health education activities. The average score on the pretest was 73.85, and the average score on the posttest was 93.1, indicating an enhancement in the students' knowledge of PHBS. UKS, which was inactive during the COVID-19 pandemic, has been revived through attempts to form â€œdokter kecilâ€ once more in addition to health education as a follow-up strategy for this community service activity.